Assessment of the pneumonia severity score in community-acquired and nursing and healthcare-associated pneumonia due to COVID-19. Issue 5 (May 2023) - Miyashita, Naoyuki; Nakamori, Yasushi; Ogata, Makoto; Fukuda, Naoki; Yamura, Akihisa; Ishiura, Yoshihisa
Abstract: Introduction: The Japanese Respiratory Society (JRS) pneumonia guidelines recommend simple predictive rules, the A-DROP scoring system, for assessment of the severity of community-acquired pneumonia (CAP) and nursing and healthcare-associated pneumonia (NHCAP). We evaluated whether the A-DROP system can be adapted for assessment of the severity of coronavirus disease 2019 (COVID-19) pneumonia. Methods: Data from 1141 patients with COVID-19 pneumonia were analyzed, comprising 502 patients observed in the 1st to 3rd wave period, 338 patients in the 4th wave and 301 patients in the 5th wave in Japan. Results: The mortality rate and mechanical ventilation rate were 0% and 1.4% in patients classified with mild disease (A-DROP score, 0 point), 3.2% and 46.7% in those with moderate disease (1 or 2 points), 20.8% and 78.3% with severe disease (3 points), and 55.0% and 100% with extremely severe disease (4 or 5 points), indicating an increase in the mortality and mechanical ventilation rates in accordance with severity (Cochran–Armitage trend test; p = <0.001). This significant relationship between the severity in the A-DROP scoring system and either the mortality rate or mechanical ventilation rate was observed in patients with COVID-19 CAP and NHCAP. In each of the five COVID-19 waves, the same significant relationship was observed. Conclusions: The mortality rate and mechanical ventilation rate in patients with COVID-19 pneumonia increased depending on severity classified according to the A-DROP scoring system. Our results suggest that the A-DROP scoring system can be adapted for the assessment of severity of COVID-19 CAP and NHCAP.